Optimizing Second Language Acquisition: A Focus on Influential Factors and Techniques - Nahida Abdo Naser (Emerging Trends in Languages, 2025)
The process through which individuals learn a language other than their mother tongue, usually after mastering their first language, is known as second language acquisition, or SLA. In this context, the second language refers to English, and this paper examines the factors influencing its acquisition. Reviews and research on SLA have been considered for a comprehensive study. The use of various tools and technologies for second language learning is highlighted, and their relationships are clearly established in this paper. Previous studies and controversies are explored to deepen the understanding of the concept. The factors influencing English language learning are broadly defined and reviewed in depth, providing insights into real-world applications. This paper also examines different languages to identify the factors involved in learning English. Various authors' perspectives and viewpoints are analyzed to draw specific conclusions. A secondary research methodology is employed, utilizing reviews and observations from multiple authors. The results and discussion are based on this approach, leading to a well-rounded conclusion. The study also highlights the significance of social and cultural factors in SLA, emphasizing how learners' settings affect their proficiency. Issues including exposure, age, and motivation are examined critically, with an emphasis on using creative teaching techniques to get past these obstacles. Future study directions are also suggested in order to fill in the gaps in the body of literature and promote more successful English learning frameworks around the world.
Keywords: Creative teaching techniques; Variability; changes in English learning; factors influencing SLA; second language acquisition